2015
DOI: 10.1159/000371339
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Blood Pressure and Collateral Circulation in Hyperacute Ischemic Stroke Patients Treated with Intravenous Thrombolysis

Abstract: Background: The integrity of collateral circulation is a major prognostic factor in ischemic stroke. Patients with good collateral status have larger penumbra and respond better to intravenous thrombolytic therapy. High systolic blood pressure is linked with worse clinical outcome in patients with acute ischemic stroke treated with intravenous thrombolytic therapy. We studied the effect of different blood pressure parameters on leptomeningeal collateral circulation in patients treated with intravenous thrombol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 26 publications
2
27
1
1
Order By: Relevance
“…In our study, systolic blood pressure did not reach statistical significance in predicting good CS in contrast to the results of our previous report where moderately elevated systolic blood pressure was associated with good CS [26] . This discrepancy may be due to a smaller sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, systolic blood pressure did not reach statistical significance in predicting good CS in contrast to the results of our previous report where moderately elevated systolic blood pressure was associated with good CS [26] . This discrepancy may be due to a smaller sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies demonstrated inconclusive findings concerning the relationship between arterial blood pressure and collateral circulation [7,8,22]. Lima et al [7], Calleja et al [6], and Liebeskind et al [8] did not show significant association between blood pressure, collateral circulation and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Lima et al [7], Calleja et al [6], and Liebeskind et al [8] did not show significant association between blood pressure, collateral circulation and clinical outcome. Rusanen et al [22] found favorable collateral circulation was associated with moderately elevated SBP, especially in the 170-190 mm Hg range, but not reaching statistical significance. On the other hand, induce hypertension therapy has been mentioned with potential benefit on cerebral perfusion [23] and antihypertension treatment possibly linked to higher mortality [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise underlying mechanism remains unclear. Because baseline BP was measured within 24 hours after stroke onset, we considered that the protection mechanism 810 of stress-induced hypertension after stroke may amplify the efficacy of dual antiplatelet therapy, especially for those with large artery stenosis in cerebral or carotid arteries. Previous studies 11, 12 indicated that dual antiplatelet therapy with clopidogrel and aspirin was more effective than aspirin alone in reducing microembolic signals in patients with ischemic stroke or TIA due to extracranial or intracranial arterial stenosis.…”
Section: Discussionmentioning
confidence: 99%